Identification of lethal species in amanita section Phalloideae based on nucleotide signature and specific TaqMan-MGB probe and primer - Duan, Renhe; Huang, Jiahui; Zhang, Donghan; Tian, Enjing (Frontiers in Microbiology, 2024)
Amanita section Phalloideae consists of lethal toxic mushroom species, causing many fatal poisoning incidents worldwide. Molecular techniques of nucleotide signatures and single nucleotide polymorphism (SNP) detection could be used to develop a specific method for identifying lethal section (sect.) Phalloideae species. A comparison of 38 sequenced and 228 validated sequences from sect. Phalloideae species showed a 17-base pair nucleotide signature and an SNP site between the lethal and non-lethal species.38 A specific minor groove binder probe was designed based on them. The results indicated that this method exhibited excellent specificity for the lethal subgroup, good detection in samples subjected to simulated gastric digestion (60 min boiling and 120 min digestion), and a 10 pg/µL detection limit. This method enables accurate detection of target species in samples under complex conditions and can provide evidence for poisoning incidents caused by lethal sect. Phalloideae species to assist in targeted treatment strategies.